Multimodal Discourse Analysis of Cinematography in “Green Book” - Yesika Natalina Sidabutar; Immanuel Prasetya Gintings; Berlin Sibaran (RETORIKA: Jurnal Ilmu Bahasa, 2025)
"Green Book," directed by Peter Farrelly, depicts the evolving relationship between Dr. Don Shirley, an African-American pianist, and Tony "Lip" Vallelonga, an Italian-American bouncer, during a 1960s concert tour in the American South. This study employs Multimodal Discourse Analysis (MDA) and Systemic Functional Linguistics (SFL) to examine how the film conveys complex social messages about race, identity, and friendship. Utilizing theories by Halliday & Matthiessen (2013, Kress & van Leeuwen (2020), and (O’Halloran, 2011), the research focuses on 23 key scenes set in a Cadillac. The study addresses three main questions: What messages are conveyed in "Green Book"? How are these meanings realized? Why are these meanings realized in their specific social context? Findings reveal significant messages about the struggles and resilience of African Americans, realized through linguistic and visual elements. The confined space of the Cadillac symbolizes broader societal issues, emphasizing personal and cultural conflicts. This research contributes to understanding multimodal discourse analysis in film studies and provides insights for filmmakers, educators, and media analysts. "Green Book" demonstrates the power of film as a medium for social commentary and cultural reflection